Characterization of bovine-derived porous hydroxyapatite scaffold and its potential to support osteogenic differentiation of human bone marrow derived mesenchymal stem cells - Krishnamurithy, G.; Murali, M.R.; Hamdi, M.; Abbas, A.A.; Raghavendran, H.B.; Kamarul, Tunku (Elsevier, 2014)
Porous three-dimensional hydroxyapatite (HA) scaffolds were prepared using bovine cortical bone derived HA (BDHA). Analyses of the morphology, chemical composition, and phase purity of the scaffold were performed using scanning electron microscopy (SEM), micro-computer tomography (micro-CT), Fourier transform infrared spectroscopy (FTIR), energy dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD). SEM images revealed the rough and porous surface of the scaffold, while micro-CT showed the average porous volume of 76.7 +/- 0.6 and pore size of 0.04-0.25 mm. Single phase corresponding to standard HA was observed using XRD, and FTIR confirmed the presence of functional groups similar to HA. The EDX analysis revealed a Ca/P ratio of 1.61, which was comparable with HA stoichiometry. Compressive strength of the BDHA scaffold was found to be 1.3 +/- 0.09 MPa. After 14 days of human bone marrow stromal cells (hBMSCs) seeding, SEM and confocal analysis revealed cell attachment to the surface and infiltration into the pores. Alamar blue and alkaline phosphatase assays showed significantly increased cell proliferation and differentiation in the BDHA scaffold, when compared with that in the monolayer (p < 0.01). In addition, quantitative real-time polymerase chain reaction (qPCR) data confirmed the up regulation of genes involved in osteogenic differentiation of mesenchymal stem cells. Our findings indicate that BDHA scaffold provides a favorable physiological environment for enhanced cell attachment, proliferation, and osteogenic differentiation of hBMSCs. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.